2014
DOI: 10.1016/j.foodchem.2014.04.114
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of hydrophilic and lipophilic extracts of Brazilian blueberries

Abstract: Hydrophilic and lipophilic extracts of ten cultivars of Highbush and Rabbiteye Brazilian blueberries (Vaccinium corymbosum L. and Vacciniumashei Reade, respectively) that are used for commercial production were analysed for antioxidant activity by the FRAP, ORAC, ABTS and β-carotene-linoleate methods. Results were correlated to the amounts of carotenoids, total phenolics and anthocyanins. Brazilian blueberries had relatively high concentration of total phenolics (1,622-3,457 mg gallic acid equivalents per 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 31 publications
7
38
2
1
Order By: Relevance
“…Donno et al (2015) found 20.89 µmol Fe 2+ /g in the goji berry from Italy and was lower than those found in this study (Table 5). Pertuzatti et al (2014) achieved antioxidant activity of 60.9% by the β-carotene/linoleic acid method in the blueberry extracts (0.46 g/mL concentration) with similar results of this study (Table 5). …”
Section: Fruit Extracts Chemical Characterization and Antioxidant Actsupporting
confidence: 86%
See 1 more Smart Citation
“…Donno et al (2015) found 20.89 µmol Fe 2+ /g in the goji berry from Italy and was lower than those found in this study (Table 5). Pertuzatti et al (2014) achieved antioxidant activity of 60.9% by the β-carotene/linoleic acid method in the blueberry extracts (0.46 g/mL concentration) with similar results of this study (Table 5). …”
Section: Fruit Extracts Chemical Characterization and Antioxidant Actsupporting
confidence: 86%
“…This shows ethanol was the most suitable solvent for the extraction of phenolic compounds in blueberry. Pertuzatti et al (2014), studied ten blueberry Brazillian cultivars and found small amounts of TPC, those values ranged from 1.62 to 3.45 mg GAE/g of açaí. For other hand, Castrejón et al (2008) studying blueberry varieties in different ripening stages from Berlin, Germany, found high TPC levels from 17.3 to 52.6 mg GAE/g sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared to this study, A. salmiana showed intermediate values of AOX activity (369 μmol TE/g dw). In a broader comparison with 42 elite AOX plants, fruits, vegetables (Pertuzatti et al, 2014), and maize (Urias-Peraldí et al, 2013), A. salmiana leaves were considered a medium source of AOXs. Upon comparison with other crops, such as wheat (58–270 μmol TE/g dw; Malunga and Beta, 2015) or sorghum (70–204 μmol TE/g dw; Awika et al, 2009), A. salmiana presented higher values, which might constitute an alternative source of AOXs.…”
Section: Discussionmentioning
confidence: 99%
“…Blueberry and blueberry juice not only contain main dietary nutrients including minerals, sugars, and vitamins, but also are regarded as one of the most abundant and accessible sources of the bioactive components that are beneficial to the human health (Hwang et al, 2014;Seeram, 2008). There are some researches display that dietary intake of blueberry and its derived products can protect our body from various diseases including cancer, ageing, urinary disease, heart disease, memory loss, and vision problems (Pertuzatti et al, 2014;Shi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%